Faktor-faktor yang Berhubungan dengan Episode Berulang Malaria di Daerah Endemis Tinggi Malaria - Lusiyana, Novyan; Rochmah, Fitria Siwi Nur Rochmah (Jurnal Kesehatan Komunitas, 2025)
Background: Timika is an endemic area for malaria in Indonesia. A receptive environment, behavioral factors, and knowledge of the local population cause the high prevalence of malaria in Timika. Objective: This study aims to determine the prevalence of recurrent episodes of malaria and factors that influence malaria episodes in highly endemic areas.Method: This study is an observational study with a cross-sectional design. This study was conducted in Naena Muktipur Village, Timika, Papua. Subjects were obtained using a purposive sampling method that met the inclusion and exclusion criteria. Demographic data, including age, address, ethnicity, education level, and occupation, were obtained through a questionnaire. Results: The subjects were predominantly women, had a high school education, and held non-risky jobs. As many as 72% of subjects had a history of malaria > 1 time, where malaria episodes were related to gender and behavior of staying overnight in the fields. Gender is related to the level of knowledge, while marital status is associated with the level of knowledge and behavior (p <0.05). Conclusion: The prevalence of recurrent episodes in highly endemic areas is still high, where malaria episodes experienced by residents in highly endemic areas are related to factors such as knowledge levels and behavior.